2012
DOI: 10.1111/j.1741-3737.2012.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Institutional and Demographic Explanations of Women's Employment in 18 OECD Countries, 1975–1999

Abstract: This study combined demographic and institutional explanations of women's employment, describing and explaining the degree to which mothers in industrialized societies are less likely to be employed than women without children. A large number of cross‐sectional surveys were pooled, covering 18 Organisation for Economic Co‐Operation and Development countries, 192,484 observations, and 305 country‐years between 1975 and 1999. These data were merged with measures of institutional context and analyzed with multile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
93
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 31 publications
3
93
0
6
Order By: Relevance
“…Family allowances, on the other hand, were regarded a 'disincentive' for women's employment (Apps & Rees, 2004;Schwarz, 2012;Thévenon, 2011;Thévenon & Luci, 2012) and indeed found to suppress the labor force participation of mothers (Jaumotte, 2003;Nieuwenhuis, 2012Nieuwenhuis, , 2014. Thus, reconciliation policies are in line with this goal of the social investment state, whereas family support policies are not.…”
Section: Family Policies and Single Parent Poverty 20mentioning
confidence: 68%
See 3 more Smart Citations
“…Family allowances, on the other hand, were regarded a 'disincentive' for women's employment (Apps & Rees, 2004;Schwarz, 2012;Thévenon, 2011;Thévenon & Luci, 2012) and indeed found to suppress the labor force participation of mothers (Jaumotte, 2003;Nieuwenhuis, 2012Nieuwenhuis, , 2014. Thus, reconciliation policies are in line with this goal of the social investment state, whereas family support policies are not.…”
Section: Family Policies and Single Parent Poverty 20mentioning
confidence: 68%
“…Nieuwenhuis, Need and Van der Kolk (2012) found that mothers' employment was lower in countries with generous family allowances. Dingeldey (2001) and Schwarz (2012) both found the same 'disincentive' for mothers' labor market participation of tax benefits for households with children.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Career dynamics refer to the experience of upward and downward job mobility in the previous year. Because the compatibility of paid employment with fertility is, especially for women, dependent on the institutional context (Matysiak and Vignoli 2008;Nieuwenhuis, Need, and Van der Kolk 2012), the next section introduces the Netherlands as the institutional and cultural background of this study. The theoretical expectations with regard to the effects of earning potential and career dynamics on the timing of the first birth are then discussed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%